The Effect of Corporate Social Performance and Financial Performance On Corporate Social Responsibility (CSR) Disclosure As an Intervening Variable Toward Firm Value - Fanisya Alya Puteri; Lindrianasari Lindrianasari; Ninuk Dewi Kesumaningrum; Farichah Farichah (The Indonesian Journal of Accounting Research, 2018)
Abstract: This study aims to examine the effect of CSP and Financial Performance to Firm Value through CSR Disclosure as an intervening variable in an attempt to attain sustainability. The research object is the mining sector companies listed in Indonesia Stock Exchange (BEI) for the 2014-2016 period. The CSP is measured from The Corporate Performance Rating Program (the acronym is PROPER) by The Ministry of Environment in Indonesia. The Return determines the Financial Performance on Assets (ROA). CSR Disclosure is measured by CSR Disclosure score based on the guidelines known as the Global Reporting Initiative (GRI-G4). The Tobin's Q is used as the indicator of the Firm Value. The result of data analysis shows that CSP and Financial Performance has a positive significant effect on the CSR disclosure. On one side, the CSP has a significant effect on the CSR Disclosure, so do the Financial Performance. In another side, the CSP has no significant effect on the Firm Value, but Financial Performance has a positive significant effect on the Firm Value. Further, the CSR disclosure has a positive significant effect on Firm Value. As a result, CSR disclosure as an intervening variable in the relationship between CSP and Financial Performance toward Firm Value is significant. Abstrak: Penelitian ini bertujuan untuk menguji pengaruh CSP dan Kinerja Keuangan terhadap Nilai Perusahaan melalui Pengungkapan CSR sebagai variabel intervening dalam upaya untuk mencapai keberlanjutan. Objek penelitian adalah perusahaan sektor pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) untuk periode 2014-2016. CSP diukur dari Program Penilaian Peringkat Kinerja Perusahaan (akronimnya PROPER) oleh Kementerian Lingkungan Hidup di Indonesia. Pengembalian menentukan Kinerja Keuangan pada Aset (ROA). Pengungkapan TSP diukur dengan skor Pengungkapan TSP berdasarkan pedoman yang dikenal sebagai Global Reporting Initiative (GRI-G4). Q Tobin digunakan sebagai indikator Nilai Perusahaan. Hasil analisis data menunjukkan bahwa CSP dan Kinerja Keuangan memiliki pengaruh signifikan positif terhadap pengungkapan TSP. Di satu sisi, CSP memiliki efek signifikan pada Pengungkapan CSR, begitu juga Kinerja Keuangan. Di sisi lain, CSP tidak memiliki pengaruh signifikan terhadap Nilai Perusahaan, tetapi Kinerja Keuangan memiliki pengaruh positif yang signifikan terhadap Nilai Perusahaan. Selanjutnya, pengungkapan TSP memiliki pengaruh positif yang signifikan terhadap Nilai Perusahaan. Akibatnya, pengungkapan CSR sebagai variabel intervening dalam hubungan antara CSP dan Kinerja Keuangan terhadap Nilai Perusahaan adalah signifikan.